algebra II
posted by nicole and brian! .
How do you verify inverses?
the question is y=3x3...
we know how to make an inverse but how do you verify it using composition?

one way is to check to make sure that
f(f^{ 1}(x)) = x
and
f^{ 1}(f(x)) = x
For example, if
f(x) = 2x7
then solve for x to get f^{ 1}
y = 2x7
(y+7)/2 = x
so, f^{ 1}(x) = (x+7)/2
Now,
f^{ 1}(f(x)) = (f(x)+7)/2
= ((2x7)+7)/2
= (2x)/2
= x
and
f(f^{ 1}(x)) = 2f^{ 1}(x)  7
= 2*(x+7)/2  7
= x+77
= x
Using values, just plug 'em in:
f(3) = 67 = 1
f^{ 1}(1) = (1+7)/2 = 3
Respond to this Question
Similar Questions

math help1
Okay I am a little bit confused about one math question can you please Help me out? 
algebra 2
for each function, find an equasion for the inverse. then use composition to verify that the equasion you wrote is the inverse. f(x)=10x6 
algebra 2
for each function, find an equasion for the inverse. then use composition to verify that the equasion you wrote is the inverse. g(x)=6x+5 please explain how you got the answer 
algebra 2
for each function, find an equasion for the inverse. then use composition to verify that the equasion you wrote is the inverse. f(x)=14.4x 
algebra
Verify that the functions f and g are inverses of each other by showing f(g(x)) = x and g(f(x)) = x f(x) = x^3 + 5 g(x) = 3sqrtx5 ( 3 is inside check mark on the sqrt. I am sooo totally lost on these! 
pre calculus
verify functions f and g are inverses of each other by showing that f(g(x)) = x and g(f(x)) = x. f(x)= 5/(2 x) g (x) = 2  5/x 
College Algebra
Verify the function f and g, are inverses of each other by showing that f(g(x))=x and g(f(x))=x Graph the functions. f(x)=6/(1x) g(x)=(16/x) 
Precalculus
Verify that the functions f and g, are inverses of each other by showing that f(g(x))=x and g(f(x))=x. f(x)=4x^3 g(x)=^3ã4x 
Algebra Emergency
Find the inverse of 2/2x1 and verify. 
precalculus
Solve the system of equations at the right by the method of substitution. Verify your results by using a graphing utility. x2+y24x+6y5=0, x+y+5=0 answer: x=y5 (y5)2+y24(y5)2+6y5=0 y=√55, y=5√5 x+√55+5=0 x=√5 …